2018
DOI: 10.24095/hpcdp.38.2.02
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of the CANRISK tool in the identification of dysglycemia in First Nations and Métis in Canada

Abstract: CANRISK functioned well as a preliminary step for diabetes screening in a broad age range of First Nations and Métis in Canada, with an adjusted CANRISK cutoff point for individuals under 40, and with no incremental improvement from using alternative BMI/WC cut-off points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Finally, in a clinical setting, storing and administering 1 test for either sex is more efficient than having 2 sex-specific risk scores. Still, just as in our previously published sexspecific models (33), BMI group conferred the largest aOR of having dysglycemia (6.77; 95% CI, 4.32 to 10.65 for obese, class 2þ) for young adults; besides age group, this was also true in previous CANRISK studies that included a large proportion of older adults (22,28,29). Using these predictors, we created a new risk score with a naïve AUC of 73.0% (95% CI, 69.7% to 76.3%) and sensitivity and specificity of 78.8% and 54.0%, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Finally, in a clinical setting, storing and administering 1 test for either sex is more efficient than having 2 sex-specific risk scores. Still, just as in our previously published sexspecific models (33), BMI group conferred the largest aOR of having dysglycemia (6.77; 95% CI, 4.32 to 10.65 for obese, class 2þ) for young adults; besides age group, this was also true in previous CANRISK studies that included a large proportion of older adults (22,28,29). Using these predictors, we created a new risk score with a naïve AUC of 73.0% (95% CI, 69.7% to 76.3%) and sensitivity and specificity of 78.8% and 54.0%, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…The published CANRISK risk scores were used (22). As done previously (28,29), the cut point was reduced (originally 33) because of having no associated score for the 18-to 39-year-old age group in the original model. Discrimination (including AUC and receiver operating characteristic statistics) was assessed as previously described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cut-off was similar to a previous study using a sample of young Indigenous Peoples. 24 We investigated the predictive ability of CANRISK for this younger population by comparing an alternative CANRISK cut-off point of 21 points "moderate risk" to the original cutoff point of 33 points "high risk". A score equal to or above the cut-off point was classified as positive for dysglycemia risk while a score below the cut-off point was classified as negative.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study using a sample of Indigenous Peoples, similar to the current study, found that CANRISK could be used on those below the age 40 with an adjustment of the score cut-off in order to improve the tool's sensitivity and reduce false negatives for this age group. 24 When CANRISK was developed, 23 only a small number of Canadian South Asians (n=323), most of whom were 40 years or older, were included in the sample used to develop the scoring algorithm. Therefore, it has not been specifically validated among Canadian South Asians, over or under 40 years of age.…”
Section: Introductionmentioning
confidence: 99%